A toolkit for the simulation of scheduling policy in desktop grid environment - Ahmad, R. (Institute of Electrical and Electronics Engineers Inc., 2016)
Desktop Grid (DG) systems use a combination of geographically heterogeneous distributed resources to execute jobs from science and engineering projects. Organization of the distributed resources are administrated by scheduling policies. To evaluate and prove the effectiveness of DG scheduling policy, a simulator is necessary since DG is an unpredictable and unrepeatable environment. Hence, the goal of this study is to develop a desktop grid simulator toolkit for evaluating and comparing a scheduling policy efficacy over other policies. The developed toolkit is a trace driven simulator based on discrete event simulation which is implemented by prototyping methodology. The prototype and the final system is developed using Java programming language united with MySQL database. Core functionalities of the simulator are job generation, volunteer generation, generation of availability information of volunteers, simulating scheduling policy, generating graphical charts and generating reports. Â© 2015 IEEE.